Mid‐Infrared Optoelectronic Waveguide Devices with 2D Materials - Liqiang Qi; Tianping Xu; Zhengkun Xing; Si Chen; Zunyue Zhang; Tiegen Liu; Zhenzhou Cheng (Advanced Physics Research)
Abstract Mid‐infrared (Mid‐IR) integrated optics has tremendous applications in spectroscopic sensing, imaging, and ranging. Compared with visible light and near‐IR wavelengths, the study of mid‐IR photonic integrated devices is limited due to the need for more suitable materials and designs for constructing high‐performance on‐chip optoelectronic devices. Integrating emerging 2D materials with novel waveguide devices opens an avenue to boost the development of high‐performance optoelectronic waveguide devices operating in the mid‐IR wavelength range. This review summarizes the previous progress, current status, and future trends in exploring mid‐IR optoelectronic waveguide devices with 2D materials. Specifically, the authors focus on the research efforts of developing passive photonic devices, modulators, photodetectors, and light sources. Then, the challenges and prospects in this area are discussed. The paper provides a valuable reference for researchers in infrared physics, optoelectronics, integrated optics, material science, sensing, and spectroscopy.